Abstract Number ‐ 164: Clot Density as a Predictor for Successful Mechanical Thrombectomy - Yazan Radaideh; Sonam Thind (Stroke: Vascular and Interventional Neurology, 2023)
Introduction Switching mechanical thrombectomy techniques (ADAPT, SR or combination) mid procedure has the potential to prolong time to recanalization as well as increase associated healthcare costs. The basis of selecting the frontline technique still relies heavily on the operators’ preference. Conflicting results indicating the varying performance of techniques relative to clot composition have been reported. Clot composition can be estimated based on clot density calculated in Hounsfield Units (HU) on pre‐intervention CT. Identifying how various clot composites behave can aid in the decision making for selecting a frontline technique.Our objective is to determine if clot density as measured by Hounsfield units can predict successful recanalization with ADAPT and the need for rescue stentriever when using ADAPT as the first line technique. Methods Retrospective review of all patients undergoing mechanical thrombectomy with first pass ADAPT at a single urban tertiary care academic stroke center. Clot HU values were calculated on pre‐intervention scans. We evaluated the number of passes, the use of rescue SR, the post intervention TICI grade and mRS on final follow up. Results There were 167 patients that underwent MT with ADAPT as the frontline approach. 122 were excluded for inability to calculate HU on pre‐ intervention scans, most often due to contamination with contrast media. 45 patients were included in the final analysis. 18/45 (40%) required SR rescue due to incomplete recanalization with first pass ADAPT. HU were dichotomized around the mean to “high” and “low”. Higher HU value was associated higher likelihood of SR use and higher final mRS scores, these however did not reach statistical significance. There was no difference in the total number of passes or the final TICI grade. AUC and ROC did not show a correlation between HU value and the use of SR or a higher number of passes need to achieve TICI ≥ 2b recanalization. Conclusions In our patient cohort, HU value was not able to predetermine the success rate of MT using ADAPT. There was no correlation between HU value and functional outcomes of patients. Reliability of clot HU value in determining MT success with ADAPT could not be established. Other factors should be considered when selecting frontline technique in mechanical thrombectomy.